Association of Atopic Dermatitis with Depression and Suicide: A Two-Sample Mendelian Randomization Study. (3rd February 2022) - Qi, Hong-jiao; Li, Lin-Feng
Abstract : Background . Atopic dermatitis (AD) has long been hypothesized to be associated with risk of depression and suicide, but the causal relationship between them is still unclear. Objective . To evaluate the causality between AD, depression, and suicide using a Mendelian randomization (MR) approach. Method . We extracted summary-level data for AD, major depression, and suicidal ideation or attempt from published, nonoverlapping genome-wide association studies (GWAS). Inverse variance-weighted (IVW) analysis was used as the primary analysis. Alternate methods, including weighted median, MR Egger, MR pleiotropy residual sum and outlier, weighted mode, and leave-out analysis, were performed to assess pleiotropy. Results . 13 SNPs (13, 287 cases and 41, 345 controls) were selected as instrumental variables (IVs). The IVW analysis indicated a statistically significant but small causal effect of AD on major depression (OR = 1.027, 95% CI 1.004-1.050; p = 0.020 ). No significant evidence was observed for a causal effect of AD on suicide. No significant effect of pleiotropy was found. Conclusion . AD has a significant but small effect on major depression, but not on suicide.